External Force Estimation for Teleoperation Based on Proprioceptive Sensors. (31st March 2014) - del Sol, Enrique; King, Ryan; Scott, Robin; Ferre, Manuel
This paper establishes an approach to external force estimation for telerobotic control in radioactive environments by the use of an identified manipulator model and pressure sensors, without employing a force/torque sensor. The advantages of - and need for - force feedback have been well-established in the field of telerobotics, where electrical and back-drivable manipulators have traditionally been used. This research proposes a methodology employing hydraulic robots for telerobotics tasks based on a model identification scheme. Comparative results of a force sensor and the proposed approach using a hydraulic telemanipulator are presented under different conditions. This approach not only presents a cost effective solution but also a methodology for force estimation in radioactive environments, where the dose rates limit the use of electronic devices such as sensing equipment.